HUBUNGAN FAKTOR RISIKO IBU HAMIL TERHADAP KEJADIAN ABORTUS SPONTAN DI RSUD DOKTER SOEDARSO PONTIANAK TAHUN 2013 - ., Woro Asriati Nurjannah (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2013)
Background?Spontaneous abortion is a spontaneous loss of pregnancybefore 20thweek pregnancy or birthweight less than 500 grams. Theprevalence of spontaneous abortion is still high.Objective?The aims of the study was to determine the association ofmothers risk factors to spontaneous abortion.Method?Analitical cross sectional study. Data was gained from thequestionnaire filled by mothers who match with sampling criteria in DoctorSoedarso Hospital Pontianak in July 2013. Data was analyzed by Chi squareand Fisher test.Result?There were 85 repondents taken as sample. Mothers age (p=0,008),mothers parity status (p=0,015), mothers history of spontaneous abortion(p=0,034), mothers history of exposured to cigarette smoke (p=0,001), andmothers body mass index (p=0,013) were associated with spontaneousabortion.Conclusion?Mother with unreproductive age, high parity status, history ofspontaneous abortion, history of exposured to cigarette smoke, or abnormalpre-pregnancy body mass index has spontaneous abortions risk factors. Keywords: spontaneous abortion, risk factor